Circulação hidrodinâmica e transporte de sedimentos no estuário do rio Parnaíba, PI - BORGES, Kassandra Kelen (2023)
Estuaries are among the most productive and hydrologically dynamic coastal ecosystems along the continent-ocean interface, due to river discharges, precipitation effect, tidal variation and wind action. The pattern of circulation and mixing in estuarine environments is fundamental for controlling the distribution and transport of materials. This work aimed to characterize the hydrodynamic circulation and the transport of bottom and suspended sediments in the estuary of the Parnaíba River, PI, during the rainy, transition and dry periods in the year 2018. For data acquisition, 8 (eight) were determined. transversal sections to the flow and 8 (eight) hydrographic stations. Temperature, conductivity and depth parameters were measured using a CTD/Exo2 and an ADCP was used to acquire continent-ocean interaction data. Suspension Particulate Matter (SPM) concentrations were obtained by gravimetry and a Gibbs dredge was used to collect sediments. The granulometric analysis was carried out by the sieving method and treated in the R Software. And later, the samples were analyzed in the Pejrup Diagram. The variation of the thermohaline structure in the rainy period indicated intense fluvial input, while in the transition and dry periods there was a greater influence of sea water. Variations in MPS concentration between the studied periods indicated higher values in the rainy season due to the high river input and lower values in the transition and dry periods, due to the greater influence of marine water in the estuarine system. The arrangement of the TS pairs indicated the presence of two distinct water masses, one of continental origin, characterized by high temperature (T ≥ 30°C) and low salinity (S ≤ 5 g.kg-1 ) and another resulting from the mixing with coastal water. In the analyzes of the continent - ocean interactions, the Transport volume (Tv), Percentage of Fresh Water (PAD) and Time of Residence (Tr), indicated an intense flow due to the fluvial input in the rainy season, already in the seasonal periods following the saline intrusion was predominant in the estuarine system. But in general, the results indicated that the greater the percentage of fresh water, the greater the residual time, depending on the influence of the tide in the region. As for the granulometric analyzes of the bottom sediments, the Medium Sand class was predominant in the rainy season and Fine Sand in the transition and dry periods. The Pejrup Diagram classified the Parnaíba river estuary as an environment of high hydrodynamics and Sand percentages ranging from 90 - 100% and through the net balance of flows, the Parnaíba river estuary was classified as an importer.